Bebras: A Social Approach for Concept Based Learning of Informatics and Computational Thinking - Filiz Kalelioğlu; Dilek Doğan; Erinç Karataş; Yasemin Gülbahar (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The International Informatics and Computational Thinking Challenge, which is more widely known as Bebras, or Bilge Kunduz in Turkey, has become an increasingly popular event worldwide over the past 15 years, with more countries becoming involved, and reaching more students each and every year. Current participation stands at around 2,614,000 students across 45 countries. The Bilge Kunduz (Bebras) challenge is a multifunctional and wide-ranging event that focusses on computational thinking skills based on the concepts of informatics. The event has been organised in Turkey for the past five years, with participation increasing each year. In this context, the aim of the current study is to share the theoretical background of the challenge and to report on data obtained by examining the event held in Turkey over the past four years. The study group of this research study is composed of 97,494 Turkish primary school students from the 5th and 6th grades. Split by event year, the group consists of 13,784 students from the 2015 challenge, 15,678 from 2016, 24,282 from 2017, and 43,750 students from 2018 who participated in the challenge. All of the students participated voluntarily. Descriptive research method was used in this study. When the nationwide activity results were examined, it was observed that female participants were more successful than male participants, that 6th graders were more successful than 5th graders, and that private school students were more successful than those from public state schools.